Pelatihan dan Pendampingan Ecopreneurship dengan Membuat Kerajinan Tangan dari Sampah Plastik bagi pengurus PKK di Surabaya - Khamimah, Wininatin; Tegowati; Dewi Urip Wahyuni; Eka Yulianti (Jurnal Pengabdian kepada Masyarakat Khaira Ummah, 2024)
st Indonesian people, especially mothers, still have low awareness of efforts to deal with the problem of plastic waste and limited knowledge to use it into handicrafts that are worth selling. For this reason, Community Service activities are carried out by offline (during training) and by online (when mentoring through whatsapp groups and video calls). This activity aims to: a) Provide training and assistance on the dangers of plastic waste and the importance of environmental conservation efforts. b. Provide training and assistance on the use of plastic waste into handicraft products with high selling value. The implementation method is by: a. Preliminary survey on plans for community service activities to the Chair and Secretary of PKK RT 08 RW 05, Airlangga Village, Gubeng District, Surabaya. b. Identify the problems faced by the PKK Management by online. c. Conduct training according to the problems faced by PKK Management by offline about ecopreneurship. d. Provide online assistance through whatsapp group media and video calls as a follow-up to the training activities that have been provided. Community service activities for PKK Management have gone well and according to plan. This activity is beneficial for the participants. That is getting knowledge about the dangers of plastic waste for the environment and the importance of environmental conservation efforts. Also acquire skills to use plastic waste into handicraft products that are worth selling.Keywords: Ecopreneurship, plastic waste, handicrafts, PKK